2013
DOI: 10.1128/aac.02311-12
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Perturbation Action Mode and Structure-Activity Relationships of Protonectin, a Novel Antimicrobial Peptide from the Venom of the Neotropical Social Wasp Agelaia pallipes pallipes

Abstract: With the extensive use of antibiotics, multidrug-resistant bacteria emerge frequently. New antimicrobial agents with novel modes of action are urgently needed. It is now widely accepted that antimicrobial peptides (AMPs) could be promising alternatives to conventional antibiotics. In this study, we aimed to study the antimicrobial activity and mechanism of action of protonectin, a cationic peptide from the venom of the neotropical social wasp Agelaia pallipes pallipes. We demonstrated that protonectin exhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…From the results of our CD measurements we conclude that membrane-rupturing activity of a peptide seems to be more likely with a higher inducible helix content. [34] This finding is in agreement with previous studies, [35] in particular with work by Bechinger and co-workers, who used solid-state NMR spectroscopy to observe helix formation and orientation of some AMPs upon contact with lipid bilayers. [36] Other biophysical studies confirmed differential interaction of amphipathic AMPs with zwitterionic versus anionic lipids.…”
supporting
confidence: 90%
“…From the results of our CD measurements we conclude that membrane-rupturing activity of a peptide seems to be more likely with a higher inducible helix content. [34] This finding is in agreement with previous studies, [35] in particular with work by Bechinger and co-workers, who used solid-state NMR spectroscopy to observe helix formation and orientation of some AMPs upon contact with lipid bilayers. [36] Other biophysical studies confirmed differential interaction of amphipathic AMPs with zwitterionic versus anionic lipids.…”
supporting
confidence: 90%
“…It has potent antimicrobial activity against both gram positive and negative bacteria, but weak hemolytic activity [13,14]. However, the effect of protonectin on fungi cells has not been reported.…”
Section: Introductionmentioning
confidence: 97%
“…aureus membrane structure, as well loss of cell-to-cell adherence. Other Hymenopteraisolated antimicrobial peptides such as melittin , polybia-MPI (Wang et al 2013b) polybia-CP (Wang et al 2012) and protonectin (Wang et al 2013a) also show important effects on microbial membranes.…”
Section: Discussionmentioning
confidence: 99%